The probability to be persistent poor in Malaysia: new evidence from panel data - Mohamed, Zunika; Said, Rusmawati (Universiti Putra Malaysia Press, 2013)
We examine the demographic characteristics of the poor that influence chances to continue to be poor by applying the binary response variable. It is based on a country representative micro data from two waves of panel household income survey 2004 and 2007. The results show that household’s characteristics, present economics and spatial disadvantages significantly influence the chances of continued poverty. The poor are either those with large household and few income earners from East Malaysia or those with low education level. They have higher risks to be trapped in poverty. Interestingly, gender and marital status are insignificant contributing factors. To help the disadvantage group, we propose improvement of the existing programmes and policy revisions to focus on other dimensions of poverty besides income and to address social exclusion issues.